2022
DOI: 10.7326/m21-4130
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of SARS-CoV-2 Reinfection in Persons With Naturally Acquired Immunity With and Without Subsequent Receipt of a Single Dose of BNT162b2 Vaccine

Abstract: Using a national database in Israel, the incidence rates of SARS-CoV-2 reinfection in persons who were previously infected with SARS-CoV-2 but did not receive subsequent vaccination were compared with the incidence rates of SARS-CoV-2 reinfection in previously infected persons who received a single dose of the BNT162b2 messenger RNA vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 41 publications
1
61
0
2
Order By: Relevance
“…Immunogenicity studies conducted during the pre-Omicron period show a single BNT162b2 vaccine dose among previously-infected individuals elicited robust antibody and T cell responses, exceeding two-dose response in the infectionnaïve. [31][32][33][34] In epidemiological studies conducted pre-Omicron, one or two BNT162b2 doses in Israel reduced the pre-Omicron re-infection risk by ~80% compared to unvaccinated, previously-infected individuals, 35,36 and in the United Kingdom hybrid protection relative to unvaccinated, previously-uninfected individuals exceeded 90% for >1 year. 14 In Sweden, one-and two-dose hybrid protection reduced the pre-Omicron re-infection risk by 58% and 66%, persisting up to 9 months for the latter, compared to unvaccinated, previously-infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Immunogenicity studies conducted during the pre-Omicron period show a single BNT162b2 vaccine dose among previously-infected individuals elicited robust antibody and T cell responses, exceeding two-dose response in the infectionnaïve. [31][32][33][34] In epidemiological studies conducted pre-Omicron, one or two BNT162b2 doses in Israel reduced the pre-Omicron re-infection risk by ~80% compared to unvaccinated, previously-infected individuals, 35,36 and in the United Kingdom hybrid protection relative to unvaccinated, previously-uninfected individuals exceeded 90% for >1 year. 14 In Sweden, one-and two-dose hybrid protection reduced the pre-Omicron re-infection risk by 58% and 66%, persisting up to 9 months for the latter, compared to unvaccinated, previously-infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In a nationally representative survey of Americans, 19% believed that gaining immunity through contracting the disease is better than vaccination (Stecula et al, 2020). This claim found some scientific support in a large Israeli study (Gazit et al, 2022), which showed people who once had a COVID-19 infection were less likely than never-infected, vaccinated people to contract the Delta variant, develop symptoms from it, or become hospitalized with serious COVID-19 symptoms. In fact, however, data from the same study suggested that previously infected people should still receive at least one dose of the mRNA vaccine as it provides a much higher protection against reinfection than remaining unvaccinated for those who once had the virus.…”
Section: Perceptions and Attitudesmentioning
confidence: 99%
“…Previous observational studies have investigated the association between Coronavirus Disease 2019 (COVID-19) vaccination and severe acute respiratory corona virus 2 (SARS-CoV-2) reinfection, 13 but the duration and effect of protection from vaccination after a SARS-CoV-2 infection remains uncertain. Despite an estimated moderate to high natural protection against reinfection with non-Omicron variants of SARS-CoV-2, 46 data from Denmark and Qatar suggests a lower protection against reinfection with the Omicron (B.1.1.529) variant.…”
Section: Introductionmentioning
confidence: 99%